Four new records of Acrocarpous mosses for Bangladesh (Bangladesh Journal of Botany, 2015)
Two species from each of the genus Fissidens Hedw. and Hyophila Brid. are dealt with. The species are Fissidens taxifolius Hedw., F. involutus Wils. ex Mitt., Hyophila perannulata Ren. et Card. and H. rosea Williams reportd as new to the Acrocarpous moss flora of Bangladesh. A detailed taxonomic description of each species with location, date of collection, name of collector and artificial keys of species are provided. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21602 Bangladesh J. Bot. 43(3): 301-308, 2014 (December)